Implementing real-time immunometabolic assays and immune cell profiling to evaluate systemic immune response variations to Eimeria challenge in three novel layer genetic lines - Fries-Craft, Krysten; Lamont, Susan J.; Bobeck, Elizabeth A. (Frontiers in Veterinary Science, 2023)
Introduction Evaluating differences in immune responses to Eimeria spp. between poultry genetic lines could be valuable for understanding favorable traits to address coccidiosis, a costly poultry disease. The objective was to compare peripheral blood mononuclear cell (PBMC) immunometabolism and composition during Eimeria challenge in three distinct and highly inbred genetic lines; Leghorn Ghs6, Leghorn Ghs13, and Fayoumi M5.1. Methods At hatch, 180 chicks (60/ line) were placed in wire-floor cages (10 chicks/cage) and fed a commercial diet. Baseline PBMC were isolated on d21 (10 chicks/line) and 25 chicks/line were inoculated with 10X Merck CocciVac®-B52 (Kenilworth, NJ), creating 6 genetic line × Eimeria groups total. Chicks were euthanized on 1, 3, 7, and 10d post-inoculation (pi; 5 chicks/ line × Eimeria group) for PBMC isolation with body weight and feed intake recorded throughout. Immunometabolic assays to determine PBMC ATP production profiles and glycolytic activity were implemented along with flow cytometric immune cell profiling. Genetic line × Eimeria challenge, and line´challenge fixed effects were analyzed using the MIXED procedure (SAS 9.4; P ≤ 0.05). Results and Discussion Before inoculation, M5.1 chicks had 14.4-25.4% greater average daily gain (ADG) with 19.0-63.6% increased monocyte/macrophage+, Bu-1+ B cell, and CD3+ T cell populations compared to both Ghs lines (P < 0.0001) but similar immunometabolic phenotype. The Eimeria main effect reduced ADG by 61.3% from 3–7dpi (P = 0.009) except in M5.1 chicks, where no ADG difference due to challenge was found. At 3dpi, Eimeria-challenged M5.1 chicks had 28.9 and 33.2% reduced PBMC CD3+ T cells and CD3+CD8α+ cytotoxic T cells than unchallenged chicks, suggesting early and preferential recruitment from systemic circulation to tissues local to Eimeria challenge (i.e., intestine; P ≤ 0.01). Both Ghs lines displayed 46.4–49.8% T cell reductions at 10dpi with 16.5–58.9% recruitment favoring underlying CD3+CD4+ helper T cells. Immunometabolic responses in Eimeria-challenged Ghs6 and Ghs13 chicks were characterized by a 24.0–31.8% greater proportion of ATP from glycolysis compared to unchallenged counterparts at 10dpi (P = 0.04). These results suggest that variable T cell subtype recruitment timelines in addition to altered systemic immunometabolic requirements may work synergistically to determine favorable immune responses to Eimeria challenge.